Hydrophobic polymer coated sodium electric material as well as preparation method and application thereof

By covering the mixed layer of hydrophobic polymer and conductive carbon on the surface of the sodium-electric material matrix, the problems of poor air stability and low energy density of sodium-ion batteries are solved, and the efficient hydrophobicity and conductivity of the material are achieved, and the circulation of the battery is improved. performance.

CN119400820APending Publication Date: 2025-02-07GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484409.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The air stability and low energy density of sodium ion batteries are mainly due to the layered structure of sodium-electric materials being easily destroyed by water and carbon dioxide, which leads to the residual sodium on the surface absorbing water and moisture, affecting the circulating performance of the battery.

Method used

Using hydrophobic polymer coating technology, a hydrophobic polymer coating layer is formed by covering a mixed layer of hydrophobic polymer and conductive carbon on the surface of the sodium-electric material matrix to enhance the air stability and conductivity of the material.

Benefits of technology

It improves the air stability and energy density of sodium-electric materials, reduces water absorption, enhances cycling performance, and does not change the layered structure of sodium-electric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400820A_ABST
    Figure CN119400820A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a hydrophobic polymer coated sodium electric material as well as a preparation method and application thereof. The invention provides a hydrophobic polymer coated sodium electric material, which comprises a coating layer and a sodium electric material matrix, the coating layer coats the sodium electric material matrix, and the coating layer comprises hydrophobic polymer and conductive carbon. According to the hydrophobic polymer coated sodium-ion battery material provided by the invention, the air stability and the energy density of a sodium-ion battery are improved on the basis of not changing the structure of the sodium-ion battery material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a hydrophobic polymer-coated sodium battery material and a preparation method and application thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries are cheaper to use, and they also have the advantages of high safety and good low-temperature performance. However, sodium-ion batteries also have disadvantages such as low energy density and poor air stability. The layered structure of sodium electric materials is easily destroyed by carbon dioxide and water, and exposure to the air for only a few hours will destroy the structural and chemical integrity; and the air stability of positive electrode materials is crucial to the manufacturing, storage and cycle performance of batteries. The poor air stability of sodium electric materials is due to: 1. The layered structure is easy to enter moisture, and 2. The residual alkali on the surface is easy to absorb water and moisture, further deteriorating the material performance. In the prior art, the layered structure is changed by doping elements, but the incomplete sodiumization causes the residual sodium to further absorb water and moisture on the surface of the material. Therefore, it is necessary to provide a sodium electric material that improves the air stability and energy density of sodium ion batteries without changing the structure of the sodium electric material. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art of changing the bulk structure of sodium electric materials so that the residual sodium on the surface increases, water absorption causes the sodium ion battery to break during circulation, and the sodium ion battery has poor air stability and low energy density, thereby providing a hydrophobic polymer-coated sodium electric material and a preparation method and application thereof.

[0004] To this end, the present invention provides the following technical solutions.

[0005] The invention provides a hydrophobic polymer coated sodium electric material, comprising a coating layer and a sodium electric material matrix, wherein the coating layer coats the sodium electric material matrix, and the coating layer comprises a hydrophobic polymer and conductive carbon.

[0006] In an optional embodiment, the molar content of the hydrophobic polymer in the sodium-electrolyte material matrix is ​​0.05-2%;

[0007] In an optional embodiment, the hydrophobic polymer includes at least one of PDMS, PAN and PTFE;

[0008] Preferably, the number average molecular weight of the hydrophobic polymer is 10000-20000;

[0009] Preferably, the hydrophobic polymer is PDMS.

[0010] In an optional embodiment, the coating layer further comprises inorganic sodium;

[0011] Preferably, the inorganic sodium includes sodium tungstate, Na 3 Zr 2 Si 2 PO 12 、Na 3 B 5 S 9 、Na 3 V 2 (PO 4 ) 3 At least one of;

[0012] Na 3 Zr 2 Si 2 PO 12 、Na 3 B 5 S 9 、Na 3 V 2 (PO 4 ) 3 All of them can be prepared according to conventional steps in the art or purchased commercially, and can also be prepared by referring to methods provided in literature or books in the art.

[0013] Preferably, the molar content of sodium element in the inorganic sodium in the sodium electric material matrix is ​​1-10%.

[0014] In an optional embodiment, the molar content of the conductive carbon in the sodium electric material matrix is ​​0.2-2%;

[0015] Preferably, the conductive carbon includes at least one of graphite, carbon nanotubes, carbon fibers and graphene;

[0016] Preferably, the conductive carbon includes at least one of graphite and carbon nanotubes.

[0017] The present invention also provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0018] (1) preparing a sodium electrode material matrix and setting it aside; preparing a coating liquid containing a hydrophobic polymer and setting it aside;

[0019] (2) The sodium electric material matrix and the conductive carbon are mixed to obtain a mixed material, and the surface of the mixed material is coated with the hydrophobic polymer coating liquid, and then solidified to obtain a hydrophobic polymer coated sodium electric material.

[0020] In an optional embodiment, the step (2) uses an immersion method or a spraying method to coat the surface of the mixed material with the hydrophobic polymer coating liquid;

[0021] Preferably, the surface of the mixed material is coated with the hydrophobic polymer coating liquid by a spraying method;

[0022] The specific steps of the spray method include: spraying the hydrophobic polymer coating liquid into the high-mixer through an atomizer, and spraying the hydrophobic polymer coating liquid evenly onto the surface of the mixed material;

[0023] The preparation steps of the hydrophobic polymer coating liquid specifically include: dispersing the hydrophobic polymer material in a solvent to obtain the hydrophobic polymer coating liquid;

[0024] Preferably, the solvent comprises at least one of ethanol and tetrahydrofuran;

[0025] Preferably, the ethanol is anhydrous ethanol;

[0026] In an optional embodiment, the hydrophobic polymer includes at least one of PDMS, PAN and PTFE;

[0027] Preferably, the hydrophobic polymer is PDMS.

[0028] In an optional embodiment, in step (2), the mixed material further comprises inorganic sodium;

[0029] Preferably, the inorganic sodium includes nano sodium tungstate, nano Na 3 Zr 2 Si 2 PO 12 、Nano Na 3 B 5 S 9 and nano-Na 3 V 2 (PO 4 ) 3 At least one of;

[0030] Preferably, the molar ratio of the sodium element in the sodium electrical material matrix, the conductive carbon and the inorganic sodium is 100:(0.2-2.0):(1.0-10.0);

[0031] Preferably, the conductive carbon includes at least one of graphite, carbon nanotubes, carbon fibers and graphene;

[0032] Preferably, the conductive carbon includes at least one of nanographite and carbon nanotubes.

[0033] In an optional embodiment, in step (2), the mixing speed is 500-1000 rpm;

[0034] In an optional embodiment, in the step (2), the mixing time is 20-40 minutes.

[0035] In an optional embodiment, the curing is carried out under nitrogen or an inert atmosphere;

[0036] In an optional embodiment, the curing temperature is 80-100°C;

[0037] In an optional embodiment, the curing time is 1-5 hours.

[0038] In an optional embodiment, the step of preparing the sodium electric material matrix includes: mixing a sodium source and a nickel manganese hydroxide precursor, and sintering to obtain the sodium electric material matrix;

[0039] Preferably, the sintering temperature is 850-1050°C;

[0040] Preferably, the sintering is carried out in an oxygen-containing atmosphere;

[0041] Preferably, the sintering time is 10-12 hours.

[0042] Preferably, the molar ratio of the sodium element in the sodium source to the nickel manganese hydroxide precursor is (6.66-6.68):10;

[0043] Preferably, the sodium source comprises sodium carbonate.

[0044] The present invention provides an application of the hydrophobic polymer coated sodium electric material or the hydrophobic polymer coated sodium electric material prepared by the above preparation method in a sodium ion battery.

[0045] The technical solution of the present invention has the following advantages:

[0046] 1. A hydrophobic polymer-coated sodium electric material provided by the present invention comprises a coating layer and a sodium electric material matrix, wherein the coating layer coats the sodium electric material matrix, and the coating layer comprises a hydrophobic polymer and a conductive carbon. The hydrophobic polymer-coated sodium electric material provided by the present invention has a high specific discharge capacity and good cycle performance. Specifically, the hydrophobic polymer in the coating layer can achieve surface super-hydrophobicity, and will not absorb water and moisture, and has no side reactions, thereby improving the air stability of the sodium electric material, overcoming the problems of the prior art that the air stability and energy density of the sodium electric material are affected by the absorption of water and moisture by residual alkali on the surface. The conductive carbon and the hydrophobic polymer cooperate to improve the hydrophobicity of the hydrophobic polymer, and can further reduce the water absorption of the sodium electric material without changing the layered structure of the sodium electric material, and improve the air stability of the hydrophobic polymer-coated sodium electric material; at the same time, the conductive carbon has a strong conductivity, which can make up for the shortcomings of the electronic insulation of the hydrophobic polymer, so that the hydrophobic coating layer has good electronic conductivity, improves the conductivity, and can improve the energy density of the sodium electric material.

[0047] 2. The present invention provides a hydrophobic polymer coated sodium electric material, wherein the mixed material further comprises inorganic sodium, and the hydrophobic polymer and the inorganic sodium cooperate to form a gap to prevent air containing moisture from entering the gap, which can further improve the hydrophobicity. The inorganic sodium can also improve the mechanical strength of the coating layer, prevent the coating layer from being damaged, and reduce the cycle performance; the inorganic sodium can also provide additional sodium ion pathways to improve the sodium ion conductivity of the coating layer, thereby improving the energy density of the sodium electric material. The conductive carbon is preferably at least one of nanographite and carbon nanotubes; the nanographite and carbon nanotubes have a convex structure, which can further enhance the hydrophobicity of the sodium electric material, prevent the sodium electric material from being damaged due to water absorption, expose the fresh surface, increase the water absorption side reaction, and reduce the cycle performance.

[0048] 3. The present invention provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0049] (1) Prepare a sodium electric material matrix for standby use; prepare a coating liquid containing a hydrophobic polymer for standby use; (2) Mix the sodium electric material matrix and conductive carbon to obtain a mixed material, coat the surface of the mixed material with the coating liquid containing a hydrophobic polymer, and solidify to obtain a hydrophobic polymer-coated sodium electric material. The hydrophobic polymer-coated sodium electric material prepared by the present invention has a high discharge specific capacity and good cycle performance. When preparing the hydrophobic polymer-coated sodium electric material, the conductive carbon and the hydrophobic polymer cooperate with each other, the conductive carbon can make up for the defects of polymer electronic insulation, and the hydrophobic polymer can improve the hydrophobicity. The two are used in combination to reduce the water absorption of the sodium electric material, improve the air stability, and ensure the energy density of the sodium electric material; the mixed material also includes inorganic sodium, and the inorganic sodium and the hydrophobic polymer are used in combination to improve the mechanical strength, prevent the coating layer from being damaged, and affect the cycle performance, and can also provide additional sodium ion pathways, increase the electron rate, and increase the energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0051] Figure 1 1 is a cycle performance diagram of the sodium electric materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-2, wherein the horizontal axis is the number of cycles and the vertical axis is the capacity retention rate;

[0052] Figure 2 This is a SEM electron microscope image of the hydrophobic polymer-coated sodium electrode material prepared in Example 1 of the present invention;

[0053] Figure 3 This is a SEM electron microscope image of the sodium electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0054] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0055] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0056] Example 1

[0057] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0058] (1) Sodium carbonate, Ni 1 / 3 Mn 2 / 3 (OH) 2 The mixture is mixed at a molar ratio of 3.335:10, sintered at 950° C. for 10 h in an oxygen atmosphere, and mechanically crushed to obtain a sodium electric material matrix;

[0059] (2) mixing 10 mol of sodium electrode material matrix, 0.1 mol of nano-graphite, 0.1 mol of carbon nanotubes and 0.5 mol of nano-sodium tungstate in a high-speed mixer at 1000 rpm for 20 min to obtain a mixed material;

[0060] (3) 0.1 mol PDMS (number average molecular weight of about 10,000) was dispersed in 200 mL of anhydrous ethanol to prepare a hydrophobic polymer coating liquid, and the hydrophobic polymer coating liquid was sprayed into a high-mixer through an atomizer. The hydrophobic polymer coating liquid was evenly sprayed onto the surface of the mixed material at 1000 rpm in the high-mixer; the mixture was cured at 80° C. for 1 h under an argon atmosphere to obtain a hydrophobic polymer-coated sodium electrode material.

[0061] The SEM electron microscope image of the hydrophobic polymer coated sodium electrode material prepared in this embodiment is shown in Figure 2 .

[0062] Example 2

[0063] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0064] (1) Sodium carbonate, Ni1 / 3 Mn 2 / 3 (OH) 2 The mixture is mixed at a molar ratio of 3.335:10, sintered at 950° C. for 10 h in an oxygen atmosphere, and mechanically crushed to obtain a sodium electric material matrix;

[0065] (2) 10 mol of sodium electrode material matrix, 0.05 mol of nano-graphite, 0.05 mol of carbon nanotubes and 0.5 mol of nano-sodium tungstate were placed in a high-speed mixer and mixed at 1000 rpm for 20 min to obtain a mixed material;

[0066] (3) 0.05 mol PDMS (number average molecular weight is about 20000) is dispersed in 200 mL of anhydrous ethanol to prepare a hydrophobic polymer coating liquid, and the hydrophobic polymer coating liquid is sprayed into a high-mixer through an atomizer. The hydrophobic polymer coating liquid is evenly sprayed onto the surface of the mixed material at 1000 rpm in the high-mixer; the mixture is cured at 80°C for 1 hour under an argon atmosphere to obtain a hydrophobic polymer-coated sodium electrode material.

[0067] Example 3

[0068] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0069] (1) Sodium carbonate, Ni 1 / 3 Mn 2 / 3 (OH) 2 Mix according to a molar ratio of 3.335:10, sinter at 1050° C. for 10 h in an oxygen atmosphere, and mechanically crush to obtain a sodium electric material matrix;

[0070] (2) 10 mol of sodium electrode material matrix, 0.025 mol of nanographite, 0.025 mol of carbon nanotubes and 0.05 mol of nano-Na 3 Zr 2 Si 2 PO 12 Mixing in a high speed mixer at 500 rpm for 40 min to obtain a mixed material;

[0071] (3) 0.1 mol PDMS (about 20,000 number average molecular weight) was dispersed in 200 mL tetrahydrofuran to prepare a hydrophobic polymer coating liquid, and the hydrophobic polymer coating liquid was sprayed into a high-mixer through an atomizer. The hydrophobic polymer coating liquid was evenly sprayed onto the surface of the mixed material at 1000 rpm in the high-mixer; the mixture was cured at 100° C. for 5 h under an argon atmosphere to obtain a hydrophobic polymer-coated sodium electrode material.

[0072] Example 4

[0073] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material, comprising the following steps:

[0074] (1) Sodium carbonate, Ni 1 / 3 Mn 2 / 3 (OH) 2 The mixture is mixed at a molar ratio of 3.335:10, sintered at 850° C. for 10 h in an oxygen atmosphere, and mechanically crushed to obtain a sodium electric material matrix;

[0075] (2) 10 mol of sodium electrode material matrix, 0.05 mol of nano-graphite, 0.05 mol of carbon nanotubes and 0.1 mol of nano-sodium tungstate were mixed in a high-speed mixer at 500 rpm for 20 min to obtain a mixed material;

[0076] (3) 0.1 mol PDMS (number average molecular weight is about 15000) is dispersed in 200 mL of anhydrous ethanol to prepare a hydrophobic polymer coating liquid, and the hydrophobic polymer coating liquid is sprayed into a high-mixer through an atomizer. The hydrophobic polymer coating liquid is evenly sprayed onto the surface of the mixed material at 1000 rpm in the high-mixer; the mixture is cured at 80°C for 1 hour under an argon atmosphere to obtain a hydrophobic polymer-coated sodium electrode material.

[0077] Example 5

[0078] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material, which differs from Embodiment 1 in that 0.1 mol of carbon fiber and 0.1 mol of graphene are used in molar amounts to replace 0.1 mol of nanographite and 0.1 mol of carbon nanotubes.

[0079] Example 6

[0080] This embodiment provides a method for preparing a hydrophobic polymer-coated sodium electrode material. The difference from Example 1 is that 0.1 mol PAN (number average molecular weight is about 10,000) is dispersed in 200 mL of anhydrous ethanol to prepare a hydrophobic polymer coating liquid, which replaces the hydrophobic polymer coating liquid in Example 1.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing a sodium electric material, comprising the following steps:

[0083] (1) Sodium carbonate, Ni 1 / 3 Mn 2 / 3 (OH) 2 The mixture is mixed in a molar ratio of 3.335:10, sintered at 950° C. for 10 h in an oxygen atmosphere, and mechanically crushed to obtain a sodium electric material.

[0084] The SEM electron microscope image of the sodium electrode material prepared in this comparative example is shown in Figure 3 .

[0085] Comparative Example 2

[0086] This comparative example provides a method for preparing a sodium electric material, comprising the following steps:

[0087] (1) Sodium carbonate, Ni 1 / 3 Mn 2 / 3 (OH) 2 The mixture is mixed at a molar ratio of 3.335:10, sintered at 950° C. for 10 h in an oxygen atmosphere, and mechanically crushed to obtain a sodium electric material matrix;

[0088] (2) 10 mol of sodium electric material matrix, 0.1 mol of nanographite, 0.1 mol of carbon nanotubes and 0.5 mol of sodium tungstate were mixed in a high-speed mixer at 1000 rpm for 20 min to prepare a sodium electric material.

[0089] Test Case

[0090] This test example provides the performance test of the sodium electric materials prepared in each embodiment and comparative example, as follows:

[0091] (1) Moisture test: The initial moisture value was measured by Karl Fischer trace water test. The materials prepared in the above embodiments and comparative examples were exposed for 1 hour in an environment of 25°C and 30% humidity. The moisture value was then measured by Karl Fischer trace water test after being exposed for 1 hour in a constant temperature and humidity environment.

[0092] (2) Electrochemical properties of sodium electrochemical materials:

[0093] Assembling the battery: the positive electrode material, carbon black and PVDF prepared by the above preparation method are mixed in a mass ratio of 90:5:5 to obtain a positive electrode mixed powder, and an NMP solution of 50% by mass of the positive electrode mixed powder is added, stirred and mixed evenly, coated, dried, and rolled into a positive electrode sheet;

[0094] Hard carbon, SBR styrene-butadiene rubber, and CMC carboxymethyl cellulose are mixed in a mass ratio of 90:5:5 to obtain a negative electrode mixed powder, and a pure water solution of 50% by mass of the negative electrode mixed powder is added, stirred and mixed evenly, coated, dried, and rolled to form a negative electrode sheet;

[0095] The positive electrode sheet containing the modified super-hydrophobic polymer coated sodium electrode material, the separator, and the hard carbon negative electrode sheet are stacked, wound, and loaded into the battery shell in sequence, and a 1 mol / L NaPF 6 and 1 mol / L LiPF 6 The electrolyte is obtained after sealing and welding.

[0096] Test method:

[0097] (1) 0.2C discharge specific capacity measurement: The battery was charged at 0.2C and discharged once at 0.2C. The results are shown in Table 1.

[0098] (2) 0.5C discharge specific capacity measurement: The battery was charged at 0.5C and discharged at 0.5C once. The results are shown in Table 1.

[0099] (3) 1C discharge specific capacity measurement: The battery was charged at 1C and discharged at 1C once. The results are shown in Table 1.

[0100] (4) Cycle performance test method: The battery was charged at 1C and discharged at 1C for 500 cycles. The results are shown in Table 1 and Figure 1 .

[0101] Table 1 Performance results of various embodiments and comparative examples

[0102]

[0103]

[0104] As can be seen from Table 1, the 0.2C discharge specific capacity of the hydrophobic polymer-coated sodium electric material prepared by the present invention is greater than 140.2 mAh / g, the 0.5C discharge specific capacity is greater than 128.5 mAh / g, the 1C discharge specific capacity is greater than 115.3 mAh / g, and the 500 cycle performance is greater than 70.9%.

[0105] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the present embodiment does not change the layered structure of the sodium electric material, but coats a coating layer composed of inorganic sodium, conductive carbon material and hydrophobic polymer outside the sodium electric material matrix; from the comparison of the initial moisture value and the moisture value after standing at constant temperature and humidity for 1 hour, the prepared hydrophobic polymer-coated sodium electric material has good hydrophobicity, does not absorb water and moisture after standing in the air, has high 0.2C discharge specific capacity, 0.5C discharge specific capacity and 1C discharge specific capacity, and has good cycle performance after 500 cycles.

[0106] Specifically, it can be seen from Comparative Example 1 that the sodium electric material without a coating layer has a decreased 0.2C discharge specific capacity, a 0.5C discharge specific capacity, and a 1C discharge specific capacity, and a significantly decreased cycle performance; from Comparative Example 2, it can be seen that the coating layer contains only conductive carbon and inorganic sodium, and its 0.2C discharge specific capacity, 0.5C discharge specific capacity, 1C discharge specific capacity and cycle performance are significantly reduced, indicating that the coating layer contains hydrophobic polymers, which can significantly improve the electrochemical properties of the sodium electric material, enhance the hydrophobicity of the sodium electric material, and thus enhance its air stability.

[0107] By comparing Example 1 with Example 5, it can be seen that the conductive carbon is preferably at least one of nanographite and carbon nanotubes; the use of nanographite and / or carbon nanotubes as conductive carbon-coated sodium-electrolyte materials has higher 0.2C discharge specific capacity, 0.5C discharge specific capacity, and 1C discharge specific capacity, and the cycle performance after 500 cycles is significantly improved. By comparing Example 1 with Example 6, it can be seen that the hydrophobic polymer is preferably PDMS, and the use of PDMS-coated sodium-electrolyte materials has higher electrochemical performance.

[0108] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A hydrophobic polymer coated sodium electrode material, characterized in that: The invention comprises a coating layer and a sodium electric material matrix, wherein the coating layer covers the sodium electric material matrix, and the coating layer comprises hydrophobic polymer and conductive carbon.

2. The hydrophobic polymer-coated sodium electrode material according to claim 1, characterized in that: The molar content of the hydrophobic polymer in the sodium-electrolyte material matrix is ​​0.05-2%; Preferably, the hydrophobic polymer includes at least one of PDMS, PAN and PTFE; Preferably, the number average molecular weight of the hydrophobic polymer is 10000-20000; Preferably, the hydrophobic polymer is PDMS.

3. The hydrophobic polymer-coated sodium electrode material according to claim 1 or 2, characterized in that: The coating layer also includes inorganic sodium; Preferably, the inorganic sodium includes sodium tungstate, Na3Zr2Si2PO 12 , Na3B5S9, Na3V2(PO4)3; Preferably, the molar content of sodium element in the inorganic sodium in the sodium electric material matrix is ​​1-10%.

4. The hydrophobic polymer-coated sodium electrode material according to any one of claims 1 to 3, characterized in that: The molar content of the conductive carbon in the sodium electric material matrix is ​​0.2-2%; Preferably, the conductive carbon includes at least one of graphite, carbon nanotubes, carbon fibers and graphene; Preferably, the conductive carbon includes at least one of graphite and carbon nanotubes.

5. A method for preparing a hydrophobic polymer-coated sodium electrode material, characterized in that: The steps include: (1) preparing a sodium electrode material matrix and setting it aside; preparing a coating liquid containing a hydrophobic polymer and setting it aside; (2) The sodium electric material matrix and the conductive carbon are mixed to obtain a mixed material, and the surface of the mixed material is coated with the hydrophobic polymer coating liquid, and then solidified to obtain a hydrophobic polymer coated sodium electric material.

6. The preparation method according to claim 5, characterized in that: The step (2) uses an immersion method or a spraying method to coat the surface of the mixed material with the hydrophobic polymer coating liquid; Preferably, the surface of the mixed material is coated with the hydrophobic polymer coating liquid by a spraying method; Preferably, the hydrophobic polymer includes at least one of PDMS, PAN and PTFE; Preferably, the hydrophobic polymer is PDMS.

7. The preparation method according to claim 6, characterized in that: In the step (2), the mixed material further comprises inorganic sodium; Preferably, the inorganic sodium includes nano sodium tungstate, nano Na3Zr2Si2PO 12 , at least one of nano Na3B5S9 and nano Na3V2(PO4)3; Preferably, the molar ratio of the sodium element in the sodium electrical material matrix, the conductive carbon and the inorganic sodium is 100:(0.2-2.0):(1.0-10.0); Preferably, the conductive carbon includes at least one of graphite, carbon nanotubes, carbon fibers and graphene; Preferably, the conductive carbon includes at least one of nanographite and carbon nanotubes.

8. The preparation method according to claim 5, characterized in that: The curing is carried out under nitrogen or an inert atmosphere; and / or, The curing temperature is 80-100°C; and / or, The curing time is 1-5h.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The steps of preparing the sodium electric material matrix include: mixing a sodium source and a nickel manganese hydroxide precursor, and sintering to obtain the sodium electric material matrix; Preferably, the molar ratio of the sodium element in the sodium source to the nickel manganese hydroxide precursor is (6.66-6.68):10; Preferably, the sodium source comprises sodium carbonate.

10. Use of the hydrophobic polymer coated sodium electric material according to any one of claims 1 to 4 or the hydrophobic polymer coated sodium electric material prepared by the preparation method according to any one of claims 5 to 9 in sodium ion batteries.